Smart Crop Selection: A Machine Learning Approach for Seasonal Farming - Shafi, Dr.R.Mahammad; K, Dr.Lakshmaiah; M., Dr.Roshini (International Journal of Innovative Research in Advanced Engineering, 2025)
Agriculture is the backbone of the economy, but unpredictable climate conditions pose significant challenges to crop production. Our Smart Crop Selection System addresses this issue by analyzing soil and climate data to provide farmers with accurate, seasonal recommendations. Leveraging Random Forest and XGBoost algorithms, the system considers key parameters like soil nutrients, pH, temperature, humidity, and rainfall. A user-friendly web interface offers interactive visualizations, enabling farmers to make informed decisions. Real-time model training ensures continuous improvement, adapting to new data and climate patterns. Our system outperforms traditional approaches, empowering farmers with reliable, data-driven insights to optimize crop yields. By providing accurate crop recommendations, our system helps farmers adapt to changing climate conditions, enhancing agricultural productivity and sustainability. This innovative approach has the potential to transform agricultural decision-making, promoting sustainable farming practices and improving farmers' livelihoods. With its robust performance and user-centric design, our system is poised to make a significant impact in the agricultural sector, supporting farmers in making data-driven decisions for better crop yields and resource allocation. This leads to improved productivity and sustainability.